2013
DOI: 10.1063/1.4794768
|View full text |Cite
|
Sign up to set email alerts
|

Thermal neutron detection using a silicon pad detector and 6LiF removable converters

Abstract: A semiconductor detector coupled with a neutron converter is a good candidate for neutron detection, especially for its compactness and reliability if compared with other devices, such as (3)He tubes, even though its intrinsic efficiency is rather lower. In this paper we show a neutron detector design consisting of a 3 cm × 3 cm silicon pad detector coupled with one or two external (6)LiF layers, enriched in (6)Li at 95%, placed in contact with the Si active surfaces. This prototype, first characterized and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…We have already proved that this detector can be operated in such a double-converter configuration [10], but for the current tests we have chosen to use it in single-converter configuration to simplify the installation and replacement of the several substrates used. The detector, with and without a converter installed, is shown in Figure 1.…”
Section: Silicon Detectormentioning
confidence: 99%
See 2 more Smart Citations
“…We have already proved that this detector can be operated in such a double-converter configuration [10], but for the current tests we have chosen to use it in single-converter configuration to simplify the installation and replacement of the several substrates used. The detector, with and without a converter installed, is shown in Figure 1.…”
Section: Silicon Detectormentioning
confidence: 99%
“…The layer thickness was measured by means of the change in the oscillation frequency of a quartz as the 6 LiF is evaporated onto it [11]. The reliability of the thickness measurements was checked by measuring the energy loss of alpha particles from a known source when crossing a converter layer deposited onto a suitably thin known substrate [10]. The thickness precision resulted of the order of a few percent, as well as its uniformity, checked on 5 different points.…”
Section: The Convertersmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the detection efficiency, it depends on the energy loss of the two reaction products inside the converter itself and in the dead layer of the silicon detector, and on the electronic threshold. An accurate calculation was performed in [8], giving a value around 75%. Under the described configuration a thermal neutron impinging on the detector will have a ≈1.5% probability of being detected.…”
Section: A Silicon Pad For Neutron Detectionmentioning
confidence: 99%
“…In a previous paper [7] it was shown that the use of a fully depleted silicon charged particle detector, in combination with a 6 LiF neutron converter film, can be successfully exploited to detect thermal neutrons with a reasonable efficiency, as also suggested by other authors [8], [9]. The neutron conversion mechanism is based on the well known reaction (1) which is the only possible decay channel following the neutron capture in 6 Li, and is free of gamma rays.…”
Section: Introductionmentioning
confidence: 99%